The role of executive functions in the pragmatic skills of children age 4–5 - Blain-Brière, Bénédicte; Bouchard, Caroline; Bigras, Nathalie (Frontiers in Psychology, 2014)
Several studies suggest that pragmatic skills (PS) (i.e., social communication) deficits may be linked to executive dysfunction (i.e., cognitive processes required for the regulation of new and complex behaviors) in patients with frontal brain injuries. If impairment of executive functions (EF) causes PS deficits in otherwise healthy adults, could this mean that EF are necessary for the normal functioning of PS, even more so than cognitive maturation? If so, children with highly developed EF should exhibit higher levels of PS. This study aimed to examine the link between EF and PS among normally developing children. A secondary goal was to compare this relationship to that between intellectual quotient (IQ) and PS in order to determine which predictor explained the most variance. Participants were 70 French-speaking preschool children (3;10–5;7 years old). The PS coding system, an observational tool developed for this study, was used to codify the children's PS during a semi-structured conversation with a research assistant. Five types of EF processes were evaluated: self-control, inhibition, flexibility, working memory and planning. IQ was estimated by tallying the scores on a receptive vocabulary test and a visuoconstructive abilities test. The results of the test of differences between correlation coefficients suggest that EF contributed significantly more than IQ to the PS exhibited by preschoolers during conversation. More specifically, higher inhibition skills were correlated with a decrease in talkativeness and assertiveness. EF also appeared to foster quality of speech by promoting the ability to produce fluid utterances, free of unnecessary repetition or hesitation. Moreover, children with a high working memory capacity were more likely to formulate contingent answers and produce utterances that could be clearly understood by the interlocutor. Overall, these findings help us better understand how EF may assist children in everyday social interactions.